Managerial and Decision Economics (JSTOR)
Managerial and Decision Economics is an international journal of research and progress in management economics. The journal publishes articles applying economic reasoning to managerial decision making. Compared to other journals in economics, the focus of this journal is more normative than positive and the viewpoint is focused on managerial efficiency rather than on social welfare.
Keywords: Business, Business & Economics, Economics, Management & Organizational Behavior